DESIGN STRATEGY OF BEKASI RAILWAY STATION DEVELOPMENT BY SPACE CIRCULATION PRINCIPAL - Iqbal Dwi Hendarto; Suparno Suparno; Samsudi Samsudi (Universitas Sebelas Maret Surakarta, 2018)
Building development is an activity of planning and redesign a building to produce a new physical without altering a particular function or location. The development of railway station made the effort to redesign the railway station while still maintaining the principles and functions of the railwail station building in accordance with standard guide of railway station building. Bekasi City Railway Station is present as a place of activity that gives a big influence for train users in doing activities conveniently through the principles of development and standardization of station. Designing at Railway Station in Bekasi City is needed in realizing the quality of comfort and sustainability of the projection of the number of users within a certain period of time. The method applied in this research, among others, begin with the appointment of number of ideas and phenomena related to railway stations, collection of data and literature that resulted in analysis as a guide in the Development of Railway Station in Bekasi City. From analysis that has been produced through research method, and result of applying The Principle of Development Railway Station in Bekasi City which embodies through the development of space, mass management, building facade.